‘Tactile qualities’ - Andrew Eastman (Sillages Critiques)
In attempting to define what constitutes, for him, the modernity of the poem, William Carlos Williams wrote, in a well-known passage of his Autobiography (1951), “It is the making of that step, to come over into the tactile qualities, the words themselves beyond the mere thought expressed, that distinguishes the modern”. This passage may be understood as referring to what critics have seen as a central principle of modernism, calling attention to language itself as medium. But “tactile” cannot be understood without evoking the problematics of touch explored in Williams’s In the American Grain (1925), and according to which true democracy requires “Men intact—with all their senses waking”. This article is an attempt to understand how the expression “tactile qualities” may be applied to Williams’s writing. Lexemes with “tactile” meaning function as a way of projecting the speaker of the poem into the “objects” he describes; at the same time, the imagination of touch determines a specific mode of orality, motivating signifiers and organizing in discourse what Saussure calls “le sentiment de la langue”. Rather than as a mimetic practice, Williams’s tactile language is seen here as the continuity of grammar and lexicon, functioning as a poetics of English, as a way of thinking about the relations between subjectivation and the body.